Pengaruh Profitabilitas, Hutang dan Ukuran Perusahaan terhadap Nilai Perusahaan Makanan dan Minuman - Pranata Eka Putra, I Putu; Pande Dwiana Putra, I Made (E-Jurnal Akuntansi; Vol 30 No 8 (2020), 2020)
The purpose of this study is to obtain empirical evidence of the influence of profitability, debt, and company size on the value of food and beverage companies. This research was conducted in all food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2018 period, amounting to 13 sample companies. The sampling method used in this study was purposive sampling and data analysis techniques in this study used multiple linear regression analysis. Based on the analysis conducted, it was found that profitability, debt, and company size had a positive effect on firm value. Keywords: Profitability; Debt; Company Size; The Value Of The Company.